An N-heterocyclic carbene based MOF catalyst for Sonogashira cross-coupling reaction. Issue 7 (25th February 2016) - Ezugwu, Chizoba I.; Mousavi, Bibimaryam; Asrafa, Md. Ali; Mehta, Akshay; Vardhan, Harsh; Verpoort, Francis
Abstract : The post-synthetic modification of azolium containing MOFs generated a new heterogeneous N-heterocyclic carbene catalyst (1 -Pd), which is very active for Sonogashira cross coupling reaction. Abstract : The post-synthetic modification of azolium containing MOFs generated a new heterogeneous N-heterocyclic carbene catalyst (1 -Pd), which is very active for Sonogashira cross coupling reaction.